Muscle Precursor Cells for the Restoration of Irreversibly Damaged Sphincter Function - Daniel Eberli; Tamer Aboushwareb; Shay Soker; James J. Yoo; Anthony Atala M.D. (Cell Transplantation, 2012)
Multiple modalities, including injectable bulking agents and surgery, have been used to treat stress urinary incontinence. However, none of these methods is able to fully restore normal striated sphincter muscle function. In this study, we explored the possibility of achieving functional recovery of the urinary sphincter muscle using autologous muscle precursor cells (MPCs) as an injectable, cell-based therapy. A canine model of striated urinary sphincter insufficiency was created by microsurgically removing part of the sphincter muscle in 24 dogs. Autologous MPCs were obtained, expanded in culture, and injected into the damaged sphincter muscles of 12 animals. The animals were followed for up to 6 months after injection, and urodynamic studies, functional organ bath studies, ultrastructural and histological examinations were performed. Animals receiving MPC injections demonstrated sphincter pressures of approximately 80% of normal values, while the pressures in the control animals without cells dropped and remained at 20% of normal values. Histological analysis indicated that the implanted cells survived and formed tissue, including new innervated muscle fibers, within the injected region of the sphincter. These results indicate that autologous muscle precursor cells may be able to restore otherwise irreversibly damaged urinary sphincter function clinically.